2021
DOI: 10.1016/j.isci.2021.103018
|View full text |Cite
|
Sign up to set email alerts
|

Encephalopathy-causing mutations in Gβ1 (GNB1) alter regulation of neuronal GIRK channels

Abstract: Summary Mutations in the GNB1 gene, encoding the Gβ 1 subunit of heterotrimeric G proteins, cause GNB1 Encephalopathy. Patients experience seizures, pointing to abnormal activity of ion channels or neurotransmitter receptors. We studied three Gβ 1 mutations (K78R, I80N and I80T) using computational and functional approaches. In heterologous expression models, these mutations did not alter the coupling between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 87 publications
3
22
0
Order By: Relevance
“…In line with the increased GABA B -GIRK signaling in Gnb 1 K78R/+ neurons, we show in Xenopus oocytes that G β 1K78R exerts a GoF toward GIRK1/2 and GIRK2 activation at physiologically relevant mild G β RNA doses, owing to higher surface expression of G β K78R compared with G β WT , in a wide range of G βγ expression levels ( Figure 6 ). The gain-of-expression of G β K78R was confirmed in our follow-up work, which also demonstrated that the K78R mutation does not affect the coupling of Gα i/o βγ to GPCRs and the G βγ regulation of voltage-gated Ca 2+ channels, Ca V 2.2 (Reddy et al, 2021 ), supporting the hypothesis that a defective G βγ -GIRK signaling plays an important role in the pathological neuronal function in K78R. However, in the case of GIRK1/2, there was a significant LoF toward GIRK1/2 at high G βγ doses, despite robust surface expression of G β K78R .…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…In line with the increased GABA B -GIRK signaling in Gnb 1 K78R/+ neurons, we show in Xenopus oocytes that G β 1K78R exerts a GoF toward GIRK1/2 and GIRK2 activation at physiologically relevant mild G β RNA doses, owing to higher surface expression of G β K78R compared with G β WT , in a wide range of G βγ expression levels ( Figure 6 ). The gain-of-expression of G β K78R was confirmed in our follow-up work, which also demonstrated that the K78R mutation does not affect the coupling of Gα i/o βγ to GPCRs and the G βγ regulation of voltage-gated Ca 2+ channels, Ca V 2.2 (Reddy et al, 2021 ), supporting the hypothesis that a defective G βγ -GIRK signaling plays an important role in the pathological neuronal function in K78R. However, in the case of GIRK1/2, there was a significant LoF toward GIRK1/2 at high G βγ doses, despite robust surface expression of G β K78R .…”
Section: Discussionsupporting
confidence: 77%
“…Overall, these results suggest that K78R is a gain-of-expression mutation, and the apparent GoF is due exclusively to higher surface expression compared to G β WT γ. Further investigation of this phenomenon showed suppression of GIRK1/2 channel expression by high doses of G β K78R γ RNA and a reduction in channel open probability (Reddy et al, 2021 ), explaining the attenuated GIRK1/2 currents at high expression levels of G β K78R γ.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations